TRANSESTERIFICAÇÃO DE BIODIESEL POR VIA ALCOÓLICA MISTA - MORAIS, Daniélly Nascimento; FISCHER, Eliane Kujat; SÁ, Igor Silva de; DE CARLI, Eduardo; MEDEIROS, Tiziana Azario de; CAVALHEIRO, Alberto Adriano (ANAIS DO ENIC, 2017)
-